2020
DOI: 10.1002/ijgo.13319
|View full text |Cite
|
Sign up to set email alerts
|

Population estimates, consequences, and risk factors of obesity among pregnant and postpartum women in India: Results from a national survey and policy recommendations

Abstract: Objective To examine prevalence, risk factors, and consequences of maternal obesity; and provide evidence on current policies and programs to manage maternal obesity in India. Methods This is a mixed‐methods study. We analyzed the National Family Health Survey (NFHS)‐4 data (2015–16) to estimate the prevalence and risk factors of obesity, followed by a desk review of literature and stakeholder mapping with interviews to develop policy guidance. Results National prevalence of obesity (defined by WHO as body mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Suboptimal nutrition and obesity are conditions that affect all women globally, spanning from high-to low-and middle-income countries. [7][8][9] The postpregnancy period presents a unique opportunity to improve maternal long-term health. Pregnancy complications can be reviewed and management plans devised to arrange follow-up to ensure that women can avail of early identification of chronic diseases such as glucose intolerance and type 2 diabetes, and cardiovascular diseases such as hypertension, ischaemic heart disease, and stroke.…”
Section: Impact Of Pregnancy On Long-term Health: Advances In Postpre...mentioning
confidence: 99%
See 1 more Smart Citation
“…Suboptimal nutrition and obesity are conditions that affect all women globally, spanning from high-to low-and middle-income countries. [7][8][9] The postpregnancy period presents a unique opportunity to improve maternal long-term health. Pregnancy complications can be reviewed and management plans devised to arrange follow-up to ensure that women can avail of early identification of chronic diseases such as glucose intolerance and type 2 diabetes, and cardiovascular diseases such as hypertension, ischaemic heart disease, and stroke.…”
Section: Impact Of Pregnancy On Long-term Health: Advances In Postpre...mentioning
confidence: 99%
“…It is estimated that one‐third of the world's population suffers from malnutrition, whether it be thinness or obesity or micronutrient deficiencies. Suboptimal nutrition and obesity are conditions that affect all women globally, spanning from high‐ to low‐ and middle‐income countries 7–9 …”
mentioning
confidence: 99%
“…In the USA, evidence suggests that obesity prevalence in women aged 20–39 is at least 31 % and may be over 61 % in women with low incomes (49) . In some regions of India, over 40 % of women may have obesity as defined by body mass index (BMI) ≥30 kg/m2 (50) . Globally, obesity prevalence is rising and is estimated to be >20 % in all women by 2025 (51,52) .…”
Section: The Current Clinical Perspectivementioning
confidence: 99%
“…A nutrition checklist that facilitates standardised nutrition assessment could support non-nutrition healthcare providers in maternity services to address nutrition as part of their routine clinical care. A similar approach has been taken in India where their government along with the UN children's fund (UNICEF) and other colleagues, has launched a treatment algorithm with checklist points to guide healthcare providers in addressing key aspects of antenatal care, including diet and weight (50) . Other regions may have locally developed tools to support nutrition assessment and feedback.…”
Section: Nutrition Counselling Toolsmentioning
confidence: 99%
“…Maternal obesity rates are disproportionately higher in Low-Middle income countries (LMICs) as India and can have adverse health outcomes for mothers and children. In India, Chopra et al analyzed the National Family and Health Survey-4 (NFHS-4) data and reported obesity among 12 % of pregnant women 20 years and above, with as high as above 40 % high in over 30 districts in multiple states [ 8 ]. Similarly, in children of South Asia, the overall prevalence of overweight and obese children was reported as 1.91 and 0.89 %, respectively [ 9 ].…”
Section: Introductionmentioning
confidence: 99%